Synthetic and spectral studies of complexing behaviour of nitrito complex of 4 [(N-4-Di ethylamino-2methyl benzalidine) amino] antipyrine. - Chaudhary, Sakshi (Recent Research in Science and Technology, 2012)
Pyrazolones have been reported to be potential extractants as well as powerful drugs, their varied chemical and physical properties. Trivalent lanthanides behave as hard acids and thus are expected to form stronger stable complexes with ligands having oxygen or N-donor atoms. Lanthanide (III) Nitrate and double the amount of ligand (4[(N-4-Diethyl amino 2-methyl benzalidene) amino] antipyrine) C23H28N4O are used for formation of complexes. The characterization of the newly synthesized complexes by molar conductance, molecular weight, magnetic susceptibility, infrared and electronic spectroscopy.